First report of c.425-1G>A mutation in ornithine aminotransferase gene causing gyrate atrophy of the choroid and retina with hyperornithinemia. Issue 5 (September 2021) - Jalali, Hossein; Najafi, Mojtaba; Khoshaeen, Atefeh; Mahdavi, Mohammad Reza; Mahdavi, Mahan
Background: Gyrate atrophy is a rare autosomal recessive inherited genetic disease. Progressive deterioration of peripheral night vision and blindness are the foremost clinical manifestations of the disease caused by mutations of ornithine aminotransferase gene. Case: The presented case was an 18-year-old male referred for a progressive reduction of visual acuity, which started when the subject was 7 years old, blurred vision, and hypotonic muscles. Observations: The findings by liquid chromatography with tandem mass spectrometry and high-performance liquid chromatography methods exhibited a high level of ornithine: 248 μmol/L (reference range: 44–206 μmol/L) and 818 μmol/L (reference: 25–123 μmol/L), respectively. After genetic counseling and conducting further investigation, a novel mutation (c.425-1G>A) in ornithine aminotransferase gene was recognized through whole exome sequencing and the mutation was verified using Sanger sequencing method, which is associated with gyrate atrophy phenotype. Conclusion: The exact mechanism of chorioretinal atrophy in hyperornithinemia is not known but the increased ornithine level is the clinical manifestation of gyrate atrophy of choroid and retina, muscle weakness, moderate mental retardation, and low cerebral creatine. Pathogenic variant in the ornithine aminotransferase gene associated with gyrate atrophy, may be beneficial as a biomarker to initial diagnosis and treatment of gyrate atrophy disease.